Dietary Inclusion of Carob Pulp (Ceratonia siliqua L.) Does Not Replace the Antioxidant Effect of Vitamin E in Lambs’ Meat to Lengthen Shelf-Life - Bottegal, Diego Nicolas; Álvarez-Rodríguez, Javier; Latorre, María Ángeles; Lobón Ascaso, Sandra (MDPI, 2025)
The objective of this study was to evaluate the impact of dietary carob pulp (Cp, Ceratonia siliqua L.) and vitamin E (Vit E) on the quality and shelf-life of light lamb meat stored for a maximum of 15 days under modified atmosphere packaging (MAP). Forty-eight lambs (half females and half entire males, 25.3 ± 0.3 kg of body weight and 83 ± 5.8 days old) were randomly selected and slaughtered after an experimental fattening period with a 2 × 2 factorial design: 0 vs. 20% Cp and 40 vs. 300 IU of Vit E/kg of diet for 41 days. The carcass traits, fatty acid (FA) profile, antioxidant content, colour, lipid oxidation, and microbial count in the meat were evaluated. Scarce interactions between Cp and Vit E were observed on most of the variables studied. The dietary inclusion of Cp did not affect carcass traits (p > 0.05) but produced minor changes in the content of branched FA and reduced the α-tocopherol content in the meat (p < 0.05), while no impact was observed on discolouration or lipid oxidation (p > 0.05). High Vit E supplementation increased the yellowness of caudal fat and the α-tocopherol content, which limited discolouration and lipid oxidation (p < 0.05). Furthermore, the High Vit E diet (without Cp) controlled the psychrotrophic bacterial count after 15 days of storage. At slaughter, males were heavier than females but had lower carcass dressing (p < 0.05). The lambs’ sex had minor impacts on the quality and shelf-life of meat. This study demonstrated that there is no synergistic interaction between Cp and Vit E on lamb meat quality and shelf-life. Including 20% of Cp in lamb diets is feasible without impairing meat quality. Nevertheless, supplementation with 300 IU of Vit E/kg of feed is essential to extend the shelf-life of meat stored under MAP.